2015
DOI: 10.25215/0301.165
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking, Reasoning, and Logical Concluding’ Abilities in relation to Academic Achievement among Indian Adolescent Students

Abstract: The aim of this study was to investigate relationship between critical thinking ability and its relevant elements such as reasoning ability and logical concluding ability in relation to academic achievement among adolescent students. Sample of this study was 625 students from high schools and pre university colleges in Mysore city of India. Data has collected by stratified random sampling. Pearson’s Correlation Coefficient, One-Way ANOVA, and Spearman’ rho Coefficient have applied to examine generated hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
0
4
0
2
Order By: Relevance
“…In the same vein, the study conducted by Roya Sherafat (2015) indicated that critical thinking skills can be considered as a key to enhance academic achievement.…”
Section: Discussionmentioning
confidence: 98%
“…In the same vein, the study conducted by Roya Sherafat (2015) indicated that critical thinking skills can be considered as a key to enhance academic achievement.…”
Section: Discussionmentioning
confidence: 98%
“…The study sample included a total of (772) students of universities in Turkey, and the critical thinking scale was CCTDI. Similarly, Sherafat (2015) indicated that there is a significant relationship between critical thinking and academic achievement, but the correlation is weak. Sherafat (2015) analyzed the data of 625 students from high schools in India by Pearson's correlation coefficient, Spearman's rho coefficient, and ANOVA.…”
Section: Definitions Of Termsmentioning
confidence: 99%
“…Similarly, Sherafat (2015) indicated that there is a significant relationship between critical thinking and academic achievement, but the correlation is weak. Sherafat (2015) analyzed the data of 625 students from high schools in India by Pearson's correlation coefficient, Spearman's rho coefficient, and ANOVA. She concluded that critical thinking enhanced academic achievement.…”
Section: Definitions Of Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indikator yang pertama yaitu memberikan alasan secara efektif dengan menggunakan berbagai penalaran sesuai dengan situasi yang ada. Kemampuan penalaran ini merupakan bagian penting dari berpikir kritis (Sherafat, 2015). Proses berpikir kritis ini dimulai dengan tahap memberikan penalaran yang logis untuk menganalisis masalah yang kemudian digunakan untuk menghasilkan kesimpulan yang logis berdasarkan bukti dan penalaran (Sherafat, 2015).…”
Section: Tabel 1 Rekap Hasil Kuisioner Untuk Komponen Kritisunclassified